Modification of the Performance of Wo3-Zro2 Catalysts by Metal Addition in Hydrocarbon Reactions - Torres, Gerardo Carlos (2012)
A study of the different hydrocarbon reactions over Ni doped WO3-ZrO2 catalysts was performed. Ni was found as NiO at low Ni concentration while at high Ni concentrations a small fraction was present as a metal. For both cases, Ni strongly modified total acidity and concentration of strong acid sites. In the cyclohexane dehydrogenation reaction, Ni addition promotes both benzene and methyl cyclopentane production. The hydroconversion activity (n-butane and n-octane) increases with the augment of total acidity produced by Ni. The selectivity to reaction products is modified according to the acid strength distribution changes produced by Ni addition.